Numerical modeling of the sand spit elongation at Cua Lo inlet - Nguyen, Quang Duc Anh (2020)
Cua Lo Inlet is a natural tidal inlet located in the Quang Nam province in the central coastal zone of Vietnam, which is connected the Truong Giang River and An Hoa lagoon to the Gulf of Tolkin (Vietnam's East Sea). In recent years, under the influence of the winter monsoon, the updrift sand spit elongation has been developed which leads to the severe deposition in the inlet. In general, when the sand spit is lengthened due to sediment accumulation on the up-drift side, breach will occur at the original location of the inlet opening to create a more efficient pathway for the water behind the sand spit (FitzGerald et al., 2001). However, due to the hydrodynamic change the breaching of sand spit in Cua Lo inlet is not incipient. This study has been investigated by the numerical models to find out the causes and the divergence of Truong Giang river flow induced by sand spit elongation under winter monsoon and river flow in flood condition influence.